Tourism and Visual Culture, Volume 2: Methods and Cases 2010
DOI: 10.1079/9781845936112.0111
|View full text |Cite
|
Sign up to set email alerts
|

Using volunteer-employed photography: seeing St David's peninsula through the eyes of locals and tourists.

Abstract: This article defines and discusses the strengths and limitations of volunteer-employed photography (VEP). VEP is one of a range of participatory research techniques which focus particularly on the visual dimension of a person's experience, be it of the place where they live or somewhere they are visiting, of a special event or of their daily routine. Three pilot surveys were undertaken in St. David's Peninsula in Great Britain in July and August 2006 on a random sample of ten tourists. Findings and literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Photographs are believed to have the capabilities to allow participants to conjure up sophisticated meanings and associations as they see and interpret their surroundings (Balomenou & Garrod, 2010;Haywood, 1990). Using visitor employed photograph (VEP) has been extensively adopted in geography and landscape planning to understand landscape perception, preferences, and outdoor recreational experiences, as well as to inform urban planning (e.g.…”
Section: Visitor Employed Photography (Vep)mentioning
confidence: 99%
“…Photographs are believed to have the capabilities to allow participants to conjure up sophisticated meanings and associations as they see and interpret their surroundings (Balomenou & Garrod, 2010;Haywood, 1990). Using visitor employed photograph (VEP) has been extensively adopted in geography and landscape planning to understand landscape perception, preferences, and outdoor recreational experiences, as well as to inform urban planning (e.g.…”
Section: Visitor Employed Photography (Vep)mentioning
confidence: 99%
“…This means that, as a method, visitor-employed photography has the potential to empower research participants since they shoot the visual themes or issues on which they wish to focus, by taking and displaying their own photographs. As Balomenou and Garrod (2010) suggest, asking participants to identify themes themselves is a more fruitful technique than researchers' attempts to make assumptions about the significance of predetermined narrative themes or issues.…”
Section: Photography Visual Representation and Travel Researchmentioning
confidence: 99%
“…Furthermore, the limited number of studies that have utilized visitor-employed photography have based their data collection on pretravel requests for photographs (e.g., Dortwart, Moore, and Leung 2009; Garrod 2009; MacKay and Couldwell 2004). This may have introduced bias in the research design in that participants might have seen their destinations in a different way had they not participated in such studies (Balomenou and Garrod 2010). Also, given the recent advances in online consumer and travel research (e.g., Kozinets 2009; Lin and Huang 2006; Magnini, Crotts, and Zehrer 2011), there is much scope to explore the extent to which unprompted, visitor-generated photography can be combined with online research to deconstruct destination image, and the extent to which such data may provide richer insights into visitors’ holistic images, and their emic representations of travel destinations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Balomenou and Garrod (2010) observed that most tourism-related research using photographs involved either volunteers who took their own pictures or photo elicitation employed within interviews. They described volunteer-based photography as a method to gain insights on touristic experiences, such as by examining what volunteers thought was of visual interest in a particular place.…”
Section: Literature Reviewmentioning
confidence: 99%